Effects of Clozapine on Perceptual Abnormalities and Sensory Gating: A Preliminary Cross-Sectional Study in Schizophrenia. Issue 2 (April 2015) - Micoulaud-Franchi, Jean-Arthur; Aramaki, Mitsuko; Geoffroy, Pierre Alexis; Richieri, Raphaëlle; Cermolacce, Michel; Faget, Catherine; Ystad, Sølvi; Kronland-Martinet, Richard; Lancon, Christophe; Vion-Dury, Jean
Abstract : Abstract: The aim of the present study was to investigate the effect of second-generation antipsychotics (clozapine or another second-generation antipsychotic) on perceptual abnormalities related to sensory gating deficit. Although clozapine is known to improve sensory gating assessed neurophysiologically, we hypothesized that patients with schizophrenia treated with clozapine would report less perceptual abnormalities related to sensory gating deficit than patients treated with other second-generation antipsychotics do. Forty patients with a diagnosis of schizophrenia were investigated (10 patients treated with clozapine and 30 patients treated with another second-generation antipsychotic drug). Perceptual abnormalities were assessed with the Sensory Gating Inventory. Sensory gating was assessed through electroencephalogram with the auditory event-related potential method by measuring P50 amplitude changes in a dual click conditioning-testing procedure. Patients treated with clozapine present normal sensory gating and report less perceptual abnormalities related to sensory gating than patients treated with other second-generation antipsychotics do. Although the cross-sectional design of this study is limited because causal inferences cannot be clearly concluded, the present study suggests clinical and neurophysiological advantages of clozapine compared with other second-generation antipsychotics and provides a basis for future investigations on the effect of this treatment on perceptual abnormalities related to sensory gating deficit in patients with schizophrenia.